If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(j + -2) = 8 + j Reorder the terms: -4(-2 + j) = 8 + j (-2 * -4 + j * -4) = 8 + j (8 + -4j) = 8 + j Add '-8' to each side of the equation. 8 + -8 + -4j = 8 + -8 + j Combine like terms: 8 + -8 = 0 0 + -4j = 8 + -8 + j -4j = 8 + -8 + j Combine like terms: 8 + -8 = 0 -4j = 0 + j -4j = j Solving -4j = j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-1j' to each side of the equation. -4j + -1j = j + -1j Combine like terms: -4j + -1j = -5j -5j = j + -1j Combine like terms: j + -1j = 0 -5j = 0 Divide each side by '-5'. j = 0 Simplifying j = 0
| 7-2r=-7 | | 10x-2=5x-8 | | -2(-x+9)=24 | | 6p+3r-4p+7r=0 | | y-4x+4=-x+x^2 | | 3x=360+3y | | 7+3t=-(t-6) | | 8.4=8y+1.2 | | 180=20r | | 33-6X=3X+19 | | 1q+1=-5q-3+8q+4 | | (30y+4)+(8y^2-15y+4)=0 | | 1+1x+1y+1m=1 | | 72=5+20 | | 2x^2+11x-67=0 | | 1x-1.87x=13.92 | | -20=-8-f-f | | 14432432+324x=234234+42x-32y | | R+15=15 | | x=-7x+9+x(4x+6) | | h+7=2h+14-9 | | 20s=89 | | t(x)=2.4x^2+90.8x+1.59 | | 9x-2x=11 | | 12j-3(j-2)=33 | | 10=8+d+d+d+d | | 4x^2y-16x^2y^2-12xy=0 | | 3x+4x=140 | | 78=3d+12-d+4 | | 0=2.4x^2+90.8x+1.59 | | 4x+42-5x=2-8x+5 | | 8(u-5)+3u=4 |